PENGAWASAN DINAS PERHUBUNGAN TERHADAP KELAYAKAN JALAN KENDARAAN BERMOTOR DI KOTA SEMARANG - T., Vencensius Dimas; Dwimawanti, Ida Hayu (Journal of Public Policy and Management Review, 2018)
Transportation is a necessity for the people to support their activities should be comfortable and safe. Every vehicle that being used must be comfortable and safe so any vehicle that operates for goods transport or public transportation should do a feasibility test. Feasibility test that performed by the Dinas Perhubungan must test the car every six months. In fact there are still many vehicles that are not safe enough in the roads are still being used, this may be a danger for the drivers and the people around the vehicle. Because of many vehicles that are not good enough to used, researchers want to see how Dinas Perhubungan supervise the feasibility test vehicle in the city of Semarang, and the obstacles that being faced and the efforts of Dinas Perhubungan in increasing the supervision. The research method that will be used is qualitative descriptive to describe how the supervision made by Dinas Perhubungan and as a research instrument the researcher uses standard, measuring activity, comparison and correction action. The results showed that supervision conducted by Dinas Perhubungan experience some obstacles such as human resources and equipment that is still manual. The advice given is the need for the addition of the number of human resources and the replacement of computerized testing tools.